Systemic administration of lipopolysaccharide impairs glutathione redox state and object recognition in male mice. The effect of PARP-1 inhibitor - Jacewicz, Maria; Czapski, Grzegorz A.; Katkowska, Inna; Strosznajder, Robert P. (Folia Neuropathologica, 2009)
Our previous data demonstrated that systemic inflammation evoked by intraperitoneal injection of lipopolysaccharide (LPS; 1 mg/kg b.w.) induces morphological and biochemical changes in the brain, including alterations of poly(ADP-ribose) polymerase-1 (PARP-1) activity and expression of several genes. In this study, the effect of systemic inflammatory response (SIR) on glutathione redox state and on cognition, spatial memory and locomotor activity was evaluated by using spectrophotometric method, object recognition test, Morris water-maze and open-field tests, respectively. The effect of PARP-1 inhibitor was included in this study. Our data indicated that SIR significantly decreases reduced glutathione (GSH) level, enhances its disulfide form (GSSG) and decreases glutathione reductase activity. Moreover, SIR affects the object recognition and locomotor activity but has negligible effect on spatial memory. PARP-1 inhibitor protects against LPS-evoked recognition impairment and significantly improves spatial memory in LPS-treated mice. The effect of PARP-1 inhibitor could be in part connected with lowering of PARP-1 involvement in regulation of transcription of several pro-inflammatory genes. Moreover, PARP-1 inhibitors may modulate glutamatergic receptor signaling that plays an important role in learning and memory.